GENETIC DETERMINATIONS OF MENTALITY - L. V. Osadcha (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is devoted to clarifying the role of physicality and psycho-physical characteristics of a person as a preconditions of the mentality forming. It is conducted a retrospective analysis of discourse on the mentality, the history of the concept, its temporal characteristics and collective conditioning. The concept of mentality has been widely studied in various fields of socio-humanities such as: history, psychology, and even marginal context of scientific discourses, including the esoteric. This study attempted to analyse the mentality phenomenon through the prism of the concept of experience. Methodology. The concept of experience was acquired by essential justification through the representatives of the phenomenological approach - the late Edmund Husserl, Maurice Merleau-Ponty, Bernhard Valdenfels. On the other hand the concept of mentality as a form of collective unconscious experience was entered to the scientific vocabulary by the representatives of the French historical science - M. Bloch, L. Febvre, J. Le Goff and others. At the intersection of these two methods, historical and phenomenological, the genetic method has been established – as a history of coverage and experience of internalization. Thanks to the application of genetic method the transition of phenomenon into the concept was examined. Novelty. The problem of change dynamics of mental phenomenon, in particular psycho-physical nature of a person, which has been only mentioned in F. Braudel works but has not received the adequate theoretical coverage, is analysed. To explain the practices of physicality and causality of this factor the action component of the cultural the overview of developments of such authors as V. Rozin (2005), M. Epstein (2005), N. Brunov (2003), A. Soares, M. Farhangmehr, A. Shoham (2007), D. Vaskul, F. Vannini Hospital (2012) was committed. Conclusions. The transition to paradoxical behaviour that is oriented on sign, and not on signalling actions, to the productive, and not to reactive activity, transformed the human physicality, as well as the person's self-image and contributed to the formation of specifically human environment of existence, which is called in the broadest sense the world of culture, but not nature.